GM-CSF production by immune cells in steady state and autoimmune neuroinflammation mapped using fate reporting mice - Azizi, Gholamreza; Rasouli, Javad; Naziri, Hamed; Gonzalez, Michael V.; Garifallou, James; Zhang, Guang-Xian; Ciric, Bogoljub; Rostami, Abdolmohamad (Frontiers in Immunology, 2025)
IntroductionGM-CSF is a pro-inflammatory cytokine that promotes an inflammatory phenotype in myeloid cells. The extent and pattern of GM-CSF expression in immune cells have not been fully elucidated. Our goal was to advance this topic using novel GM-CSF reporter/fate reporter transgenic mice.MethodsWe tracked ongoing and past GM-CSF expression in various immune cells from multiple organs, in steady-state and autoimmune inflammation of the central nervous system (CNS).ResultsThe GM-CSF expression patterns varied by cell type and organ, with CD4+, CD8+, and CD11b+ cells being the main producers. GM-CSF expression was transient and seemingly permanently lost in most cells over time. In a mouse model of CNS autoimmunity, effector memory CD4+ T cells were the dominant GM-CSF source in the CNS. A large proportion of CD4+ T cells that expressed GM-CSF also expressed CXCR6, but this chemokine receptor did not play a main role in the CNS autoimmunity. Transcriptomic analysis showed notably distinct gene expression profiles between effector memory CD4+ T cells that did and did not express GM-CSF.DiscussionThese findings identified distinct GM-CSF cellular sources across organs, highlighting the transient nature of GM-CSF expression and the correlation between its expression and the overall phenotype of effector memory CD4+ T cells.